Double-Layer Optimal Configuration Method of Hybrid Energy Storage System Based on Chaotic Ant Colony Algorithm - Jing Yuan Liu; Xu Yang; Jin Gang Guo; Da Wang; Hai Zhao; Yue Lan (Advances in Multimedia)
In order to stabilize the output fluctuation of wind power generation, this paper applies control strategy to control the action of the battery energy storage system according to the stability target, and quickly makes up for the system demand. In this paper, the optimal scheduling of new energy power system with energy storage is studied. This model predictive control is introduced into a certain system and optimized by model predictive control strategy so that the combination can match the predetermined expectations. Then, the model predictive control strategy is used to improve the schedulability of the wind farm. The objective function is to minimize the amount of action, and the composite output can track the scheduling instructions. Considering the cost, the way of storage and operation cost is optimized, and the penalty cost of wind abandonment is also reduced. Through rolling optimization and feedback correction, the model predictive control is optimized and solved, and finally, the action instructions of the storage system are obtained so that the storage output can effectively calm the wind. Power makes the combination schedulable. The optimized wind power/energy storage output is equivalent to the benign and dispatchable power supply of the power grid.